’’دی میسج آف قرآن‘‘ از محمداسد؛ کا منہج و اسلوب کا ایک جائزہ: The Review of the Method and Style of "The Message of Quran" by Muhammad Asad - Aziz, Asma; Naz, Shama; Tahseen, Fozia (Journal of Quranic and Social Studies, 2023)
The Holy Quran is the Book of Guidance and code of conduct for all mankind till the occurance of the Qiyama. The language of the Quran is Arabic, and the quality of this Arabic is quite different from Arabic that is used in daily life of Arabs. As the understanding of the Holy Quran is difficult for Arabs so it is also difficult for non-Arabs and all the people of world. So the translation of the Quran is dire need of time and Ummah that’s why the all the scholars of Muslim Ummah established their scholarships to allow its translation in the world’s languages. Likewise the Holy Quran has been translatated in the English language, George Sale translated it in English firstly. Muhammad Asad was renowed converted Muslim and Pakistani, he contributed in the Islamic Literature and wrote many though proving books on Islamic thoughts. His one main contribution is “The Message of the Quran” English translation. This research deals to analyze the style and methods of his English translation of the Quran.